Simulation and verification of a spread spectrum wireless LAN using SAW chirped delay lines - Gugler, Wolfgang; Huemer, Mario; Springer, Andreas; Pohl, Alfred; Reindl, Leonhard; Weigel, Robert; Seifert, Franz (IEEE Fifth International Symposium on Spread Spectrum Techniques and Applications, 1998)
We present a wireless spread spectrum system based on SAW chirped delay lines on LiTaO3-X112rotY operating in the ISM band at 2.45 GHz. The center frequency, transmission bandwidth, chirp rate, and data rate are 348.8 MHz, 80 MHz, ±40 MHz/μs, and 2 Mbits/s, respectively. Due to the reduction of the sidelobes of the compressed pulse to -42 dB, a high processing gain of 22 dB, and the large transmission bandwidth our system is robust against narrowband fading and noise. This paper describes the design, technology and measurement results of the used SAW chirped delay lines. The proposed communication system and simulation results are presented, measurements obtained with a hardware demonstrator are given, and the limiting factors of the data rate of our system are shown.
elib2cris::1512001600,gugler1998